The role of networking ties on contractor firm performance - Reuben anak Jagai; Muhamad Saufi Che Rusuli; Nelson Lajuni (The Malaysian Journal of Business and Economics (MJBE), 2020)
In this study, we applied the Institutional Theory to examine the direct effects of networking ties towards contractor firm performance in Sarawak, Malaysia. Non-probability purposive sampling was conducted on contractors (N = 119) to assess these correlations. By applying partial least squares-structural equation modelling, the data is then analysed using SmartPLS 3.2.9 software. The results found that business ties and government support had significant effects on the contractor firm performance. These findings provide a better understanding of the role of networking ties towards the contractor firm performance as business ties, and government support is found to be significantly related to the firm performance. Contractor firms must take advantage of the opportunities in an emerging market like Malaysia. Cultivating networking ties may be necessary to ensure the survival of firms to address demand and institutional steeplechases.